Mining & environment in India - Joshi, S. C.; Bhattacharya, G.; Pangtey, Y. P. S.; Joshi, D. R.; Dani, D. D.; Himalayan Research Group (India) (Nainital, India : Himalayan Research Group, 1988)
Collected papers.
Includes bibliographies.
Keywords: Mineral industries -- Environmental aspects -- India; Mine safety -- India; Environmental protection -- India